A drug utilization study of Prospective analysis of prescribing pattern of antimicrobials used in surgical procedures in tertiary care hospital - Manisha Bhosale; Nisharani Jadhav; Ravikumar Baradol; Raveendra D. Totad (Al Ameen Medical College, 2024)
Introduction: Antimicrobials are the most commonly prescribed group of drugs today, but the problem of its overuse or inappropriate use is a global phenomenon. Majority of the antimicrobial use is preoperative during surgical procedures. Methodology: The prescribing trends of antimicrobials used during surgical procedures were assessed in 500 patients and were compared among different types of surgeries. The surgical antimicrobial prophylaxis in clean and clean contaminated surgeries was compared with the published guidelines for prophylaxis. Results: The prescribing pattern shows that average three antimicrobials were prescribed in patients, with cephalosporins being the most commonly prescribed antimicrobial group. About 42% percent of the total antimicrobials were prescribed from outside hospital source and as many as 90.4% of the patients were prescribed one or more antimicrobial from outside the hospital source. Conclusion: There is a considerable scope for improving prescribing pattern of drugs to achieve rational and cost effective antimicrobial use.